2019
DOI: 10.1016/j.jecp.2019.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Do implicitly measured math–anxiety associations play a role in math behavior?

Abstract: The current study examined the role of implicitly measured associations (henceforth referred to as associations) between math and anxiety in adolescents' math anxiety. Previous research has shown that associations predicted behavior independent of explicit measures. In this study, it was investigated whether math-anxiety associations would be related to math anxiety and whether they predicted math behavior as well as state math anxiety independent of explicitly measured math anxiety. In addition, the domain sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 79 publications
0
12
0
Order By: Relevance
“…An assumption shared by various reliability coefficients is a linear relation between task score and trial scores. Linearity is assumed by alpha (Green et al, 2016 ), Spearman-Brown-adjusted intraclass correlation coefficient (de Vet et al, 2017 ; Hedge et al, 2018 ; Warrens, 2017 ), and Spearman-Brown-adjusted Pearson correlation (Abacioglu et al, 2019 ; Chapman et al, 2019 ; Cooper et al, 2017 ; de Hullu et al, 2011 ; Enock et al, 2014 ; Lancee et al, 2017 ; MacLeod et al, 2010 ; Schmitz et al, 2019 ; Waechter et al, 2014 ). However, task-scoring algorithms may apply a range of non-linear transformations, thereby being incompatible with these coefficients by design.…”
Section: Introductionmentioning
confidence: 99%
“…An assumption shared by various reliability coefficients is a linear relation between task score and trial scores. Linearity is assumed by alpha (Green et al, 2016 ), Spearman-Brown-adjusted intraclass correlation coefficient (de Vet et al, 2017 ; Hedge et al, 2018 ; Warrens, 2017 ), and Spearman-Brown-adjusted Pearson correlation (Abacioglu et al, 2019 ; Chapman et al, 2019 ; Cooper et al, 2017 ; de Hullu et al, 2011 ; Enock et al, 2014 ; Lancee et al, 2017 ; MacLeod et al, 2010 ; Schmitz et al, 2019 ; Waechter et al, 2014 ). However, task-scoring algorithms may apply a range of non-linear transformations, thereby being incompatible with these coefficients by design.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 1549 Dutch secondary school students participated in three studies. The original study purposes were the introduction of a math anxiety questionnaire (Study 1: n = 998, Schmitz, 2020), comparing implicit and explicit math anxiety measures (Study 2: n = 189, Schmitz et al, 2019), and relating math anxiety to other motivational and affective factors (Study 3: n = 362, Sachisthal et al, 2021). 2 Combining the data of the studies allowed for a powerful test of measurement invariance.…”
Section: Methodsmentioning
confidence: 99%
“…Math anxiety is characterized by an excessive and sometimes unreasonable fear of numerical related activities (e.g., math homework, comparing loan options), as well as fear of situations wherein the individual is concerned about possible negative evaluation (e.g., by teachers or classmates) of one’s numerical performance (e.g., during math exams; Richardson & Suinn, 1972). Thus, in terms of numerical and academic achievements, math anxiety is negatively linked to math performance (Chang & Beilock, 2016; Hembree, 1990; Ma, 1999), and math anxious individuals show lower performance on numerical tasks (Beilock et al, 2010; Choe et al, 2019; Maloney & Beilock, 2012; Passolunghi et al, 2020; Rolison et al, 2020; Schmitz et al, 2019) and poor cognitive abilities in mathematics (Rubinsten et al, 2012; Rubinsten & Tannock, 2010).…”
Section: Self-centeredness Well-being and Mindfulness: Theoretical Li...mentioning
confidence: 99%
“…For instance, it was shown that anxious participants typically rush through tasks (Ashcraft & Krause, 2007) and thus show faster and less carefully examined responses (which do not result from hampered working memory resources; see Morsanyi et al, 2014b). Additionally, math anxious individuals demonstrate reduced confidence in their performance (Jain & Dowson, 2009; Morsanyi et al, 2014a) and thus tend to select easy and low-rewarding math problems over hard and high-rewarding problems (Choe et al, 2019; Schmitz et al, 2019). Together with the shorter time they spend on math problems (Morsanyi et al, 2014a), this tendency is expected to hinder their corrective actions.…”
Section: Self-centeredness Well-being and Mindfulness: Theoretical Li...mentioning
confidence: 99%